Evaluasi Implementasi Kurikulum Merdeka (IKM) di SMK Swasta Jakarta Timur - Maman Paturahman; Muhammad Arifin Rahmanto (Mathematics Education Study Program, 2025)
This study aims to determine the effectiveness of the Implementation of the Independent Curriculum (IKM) in Private Vocational High Schools in East Jakarta. This study uses an evaluation method with the CIPP evaluation model approach (Context, Input, Process, and Product). The results of the study prove that: 1) Context, the implementers of the Independent Curriculum Implementation program, all important elements and personnel, namely the principal, educators, education personnel, parents of students and other stakeholders; 2) Input, in designing programs, implementing programs, and the performance of all personnel, especially students as learners as well as “extended output” of the entire process is very good because the support; personnel, budget, facilities, and various media are relatively complete; 3) Process, the implementation of the entire Independent Curriculum Implementation program (IKM) including the Pancasila student profile strengthening program (P5) went very well; 4) Product, performance (appraisal) of students as subjects of dynamics in the entire learning process can be witnessed at events that have been determined by the school very well and varied according to the chosen themes. Thus, the fruits of the Implementation of the Independent Curriculum (IKM) and the implementation of the Pancasila student profile strengthening program (P5) are very impressive and need to be carried out continuously.